Monoracials’ perceptions of biracials in Singapore - WEE, Sheila Xi Rui (Institutional Knowledge at Singapore Management University, 2023)
Objectives: Drawing on social identity theory, present research examined the effects of overlapping racial membership on monoracials’ categorization of biracials as in-/out-group members, as well as its impact on monoracials’ social perceptions of biracials in Singapore. Within Singapore, it is hypothesized that biracials who share racial membership with monoracials would be rated more as monoracials’ racial in-group and be evaluated more positively. Furthermore, monoracials’ positive perceptions of biracials with (vs. without) shared racial membership would be less influenced by biracials’ confrontation of racial prejudice. Method: Studies 1 (N = 242) and 2 (N = 153) sampled Chinese Singaporeans to assess their perceptions of several fictitious biracial targets. Utilizing an experimental confrontation paradigm, Studies 3 (N = 170) and 4 (N = 225) investigated the effects of confronting racial prejudice on Chinese Singaporeans’ perceptions of biracials. Results: Studies 1 and 2 revealed that Chinese Singaporeans perceive Chinese-other (vs. non-Chinese) biracials as more racially similar to themselves and were more likely to report positive social perceptions of Chinese-other biracials. Compared to non-Chinese biracials, Studies 3 and 4 found that Chinese-other biracials’ response to racial prejudice did not negatively affect Chinese Singaporeans’ perception of them. Findings revealed that Chinese–other biracials were well-liked regardless of their response to racial prejudice, demonstrating Chinese Singaporeans’ recognition of shared racial membership. Interestingly, Chinese Singaporeans increased their liking for Indian-Malay biracials when they confronted antimajority racial prejudice. Conclusion: Perceiving shared racial membership positively influenced Chinese Singaporeans’ perceptions and feelings toward biracials. Theoretical and practical implications are discussed.